2004
DOI: 10.1007/bf02702612
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity analysis of two variable DNA B components ofMungbean yellow mosaic virus-Vigna inVigna mungo andVigna radiata

Abstract: Mungbean yellow mosaic virus-Vigna (MYMV-Vig), a Begomovirus that causes yellow mosaic disease, was cloned from field-infected blackgram (Vigna mungo). One DNA A clone (KA30) and five different DNA B clones (KA21, KA22, KA27, KA28 and KA34) were obtained. The sequence identity in the 150-nt common region (CR) between DNA A and DNA B was highest (95%) for KA22 DNA B and lowest (85.6%) for KA27 DNA B. The Rep-binding domain had three complete 11-nt (5'-TGTATCGGTGT-3') iterons in KA22 DNA B (and KA21, KA28 and KA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…The fact that ICMV DNA A accumulated to high levels, regardless whether DNA B was present or not, while symptoms were much more severe upon agroinoculation with both DNAs, revealed that ICMV DNA B plays an important role in symptom development, which validates the earlier reports on symptom determination of bipartite begomoviruses [31,35,41]. The infectivity analysis of ICMV-[SeT4] in N. benthamiana plants proved that the isolate cloned from the CMD re-emergent cassava plants is infectious.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The fact that ICMV DNA A accumulated to high levels, regardless whether DNA B was present or not, while symptoms were much more severe upon agroinoculation with both DNAs, revealed that ICMV DNA B plays an important role in symptom development, which validates the earlier reports on symptom determination of bipartite begomoviruses [31,35,41]. The infectivity analysis of ICMV-[SeT4] in N. benthamiana plants proved that the isolate cloned from the CMD re-emergent cassava plants is infectious.…”
Section: Resultssupporting
confidence: 88%
“…The probe DNA was labeled with [α- 32 P] deoxycytidine triphosphate (dCTP) using the Megaprime DNA labeling system (GE Healthcare UK Ltd.). Hybridization was carried out overnight at 65 °C followed by high stringency post hybridization washes [35]. …”
Section: Methodsmentioning
confidence: 99%
“…These are closely related to each other and to MYMIV (92%) than to MYMV. The second group is hypothesized to have emerged as a result of reassortment during mixed infection in a common host [8][9][10]. It is speculated that due to high percentage sequence identity in the CR ([75%) between these two virus species and the common hosts they infect, the MYMV …”
Section: Introductionmentioning
confidence: 98%
“…We report for the first time that geminivirus DNA accumulation is reduced in transgenic plants which expressed a TrAP mutant and the wild-type Agrobacterium VirE2. Vig] DNA A and DNA B caused the yellow mosaic disease in blackgram (Vigna mungo) [5] and mungbean [30].…”
Section: Introductionmentioning
confidence: 99%